Optical Gas Sensor Fabrication Based on Porphyrin-Anchored Electrostatic Self-Assembly onto Tapered Optical Fibers - Jarzebinska, Renata; Korposh, Sergiy; James, Stephen W.; Batty, William J.; Tatam, Ralph P.; Lee, Seung-Woo (Taylor & Francis, 2012)
Tapered optical fibers with nano-assembled coatings of thicknesses of order tens of nanometres were used for the detection of ammonia gas. The film coating was composed of alternate layers of tetrakis-(4-sulfophenyl) porphine (TSPP) and poly(allylamine hydrochloride) (PAH), which were deposited using the electrostatic self-assembly process (ESA). Exposure of a PAH/TSPP nano-assembled non-adiabatic tapered optical fiber with a waist diameter of 10µm to ammonia induced significant optical changes in the transmission spectrum of the optical fiber. The fiber optic sensor showed a linear sensitivity to the concentration of ammonia in the range of 10-100ppm, with response and recovery times less than 100 and 240sec, respectively. The 3σ limit of detection (LOD) was estimated to be ca. 2ppm.